Embryonic development and larval growth of Brycon nattereri Gunther, 1864 (Characidae) and its implications for captive rearing - Maria, Alexandre N.; Ninhaus-Silveira, Alexandre [UNESP]; Orfao, Laura H.; Viveiros, Ana T. M. (Cambridge Univ Press, 2017)
The aim of this study was to describe, for the first time, the embryogenesis and larval growth of the Paraitinga Brycon nattereri Gunther, 1864 reared in captivity. After artificial fertilization, eggs were incubated at constant temperature (similar to 19 degrees C) and collected every 15 min during the first 3 h and then every 3 h until hatching. Five larvae were collected daily over 15 days for evaluation of the length, yolk sac volume and specific growth rate. The following stages of embryonic development were identified: zygote, cleavage, gastrula, segmentation and larval. The hatching occurred after 50-54 h, with larvae poorly developed and fully depigmented, devoid of mouth and swimming capacity, presenting 6.32 mm total length and 3.64 mm(3) yolk sac volume. The mouth opening was observed between days 3-4 after hatching. The yolk sac absorption was slow during the first 3 days, increasing sharply after this period, being completed on the day 11. During this period there was a decrease in the larval growth rate. After yolk sac absorption, an increase in the growth rate was observed that coincided with the start of exogenous feeding. Cannibalism was not observed during the 15 days of evaluation. The initial development of B. nattereri was slow and poorly developed larvae in relation to other Brycon species, certainly due to the lower temperature required for egg incubation and larval rearing. Other studies are needed in order to develop techniques to improve the methods of incubating eggs and feeding larvae.
Keywords: Development; Embryo; Larvae; Neotropical; Threatened fish